KANSER TANISI ALAN HASTALARDA SERUM PARAOKSONAZ VE ARİLESTERAZ SEVİYELERİ - HAFIZOĞLU, NEFSAL MAR (Fırat Üniveristesi, 2006)
Kanser tanısı alan hastalarda serum paraoksonaz ve arilesteraz seviyeleriAmaç: Çalışmada yeni tanı akciğer kanserli olgularda serum paraoksonaz(PON1) ve arilesteraz (ARE) aktiviteleri ve PON1 fenotip dağılımının sağlıklı kontrolgrubuyla karşılaştırılması amaçlandı.Gereç ve Yöntem: Yeni tanı almış akciğer kanseri (AK) grubu ve aynı yaş-cinsiyetteki sağlıklı bireylerden oluşan kontrol grubunu içeren çalışma prospektifolarak yapıldı. Her iki gruptaki 39 bireyin serum PON1 ve ARE aktiviteleri ile lipidparametreleri ölçüldü. Serum PON1/ARE aktivite oranlarına göre PON1fenotiplendirmesi yapıldı. Verilerin istatistiki değerlendirmelerinde Mann Whitney-Utesti, Student t testi ve Pearson korelasyon analizi kullanıldı.Bulgular: AK grubunda serum PON1 (p<0,001) ve ARE (p=0,018) aktivitelerikontrol grubuna göre anlamlı olarak düşüktü. Her iki grupta da PON1 enzim aktivitesiüç farklı fenotip olarak belirlendi. PON1'in düşük aktiviteli AA fenotipini taşıyanbireyler AK grubunda daha fazla iken kontrol grubunda yüksek aktiviteli BB fenotiplibireyler daha fazla idi. AK grubunda düşük aktiviteli fenotip AA, intermediateaktiviteli fenotip AB ve yüksek aktiviteli fenotip BB bireylerin serum PON1 seviyelerikontrol grubundaki aynı fenotipi taşıyan bireylerinkine göre daha düşüktü. AKgrubunda PON1/yüksek dansiteli lipoprotein (HDL) oranı kontrol grubuna göreistatistiksel olarak anlamlı düşüktü (p=0,009). Pearson korelasyon analizine göre serumHDL seviyesi ile serum PON1 seviyesi arasında AK grubunda (r=0,496, p=0,001) vekontrol grubunda (r=0,415, p=0,009) pozitif korelasyon vardı. Lipid parametrelerinindeğerlendirilmesinde total kolesterol AK grubunda kontrol grubuna göre anlamlıolarak (p=0,014) düşükken diğer lipid parametreleri istatistiki anlamlı olmayarakdüşüktü.Sonuç: AK tanısı almış hastalarda serum PON1 seviyesi ve PON1/HDLoranının azaldığı saptandı.Anahtar kelimeler: Akciğer kanseri, paraoksonaz, fenotip, antioksidan.1

The serum paraoxonase and arylesterase activities in patients with cancerObjectives: The aim of our study was to determine whether serum paraoxonase(PON1) and arylesterase (ARE) levels and phenotypes distribution is altered newdiagnosis in patients with lung cancer (LC) and to compare the values with those ofhealthy controls.Material and Methods: The study was optained prospective which consist ofthe LC group who has taken new diagnosis and healthy control group who has formedfrom the same age- and sex-matched. Serum PON1 and ARE activities and lipidparameters were measured in 39 subjects in both groups. The PON1 phenotypes aredefined according to the ratio of serum PON1/ARE activity. In statistical evaluation ofdata were performed Mann Whitney-U test, Student t test and Pearson?s correlationanalysis. P value <0.05 was accepted as significant.Results: The PON1 (p<0,001) and ARE (p=0,018) activities was found to belower in the patients with LC compared to controls. PON1 enzyme activity wasdetermined as three different phenotypes in both groups. The low activity PON1phenotype AA in the LC group was more than the control group. The high activityPON1 phenotype BB was high in the control group. Serum PON1 levels in the lowactivity phenotype AA individuals, intermediate activity phenotype AB individualsand high activity phenotype BB individuals in the LC group were lower than thesimilar phenotype individuals in the control group. The ratio of PON1/high densitylipoprotein (HDL) was statistically significant decreased in the LC group than thecontrol group (p=0,009). As the Pearson?s correlation analysis, there was a positivecorrelation between serum HDL level and serum PON1 level both control group(r=0,415, p=0,009) and LC group (r=0,496, p=0,001). The evaluation of lipidparameters the level of total cholesterol was significantly lower (p=0,014) in the LCgroup compared to the controls whereas other lipid parameters were not lowerstatistically.Conclusion: The patients with LC were determined to be lower serum PON1level and the ratio of PON1/HDL.Keywords: Lung cancer, paraoxonase, phenotype, antioxidant.2
The serum paraoxonase and arylesterase activities in patients with cancer
Keywords: Onkoloji